Household-level determinants of employment and earnings in rural Nigeria - John Chiwuzulum Odozi; Abigail Gbemisola Adeyonu (Cogent Economics & Finance, 2021)
Despite the extensive literature on rural poverty outcome, the labour employment channel has not been carefully investigated for rural Nigeria. The paper used the socioeconomic data from the three waves of the Nigerian General Household Survey Panel (2010/2011, 2012/3013 and 2015/2016 to examine the nature of household employment. By exploiting the panel nature of the data, we used a logit model and fixed effect approach to analyze the factors determining the employment expansion and earnings. From the descriptive statistics, agricultural employment sectoral share remains substantial but declined over the period considered. The study finds that much of the employment in rural Nigeria during the period 2010 to 2015 is farm self-employment. Though declining, it is two times the non-farm employment share and five times wage employment share. Wage employment is least and declining during the period covered. Findings from the econometric analysis suggest rural programmes that promote rural infrastructural, human capital development, networking, higher income and the diversity of income. It is an imperative policy goal to create an enabling environment for productivity and employment-intensive growth across all sectors of the economy particularly in agriculture.
Keywords: 330; Agriculture; earnings; households; labor Supply; poverty reduction; rural employment; structural transformation